Наследование изоферментов четырех дегидрогеназ у ели европейской (Picea abies (L.) Karst) - Привалихин, С.Н. (Промышленная ботаника, 2004)
Genetic control of enzymes of glutamatedehydrogenase (GDH), malate dehydrogenase (MDH), formiatdehydrogenase (FDH), alcoholdehydrogenase (ADH) has been studied in Norway spruce (Picea abies (L.) Karst) from 2 natural populations of Ukrainian Carpathians. Distinct electrophoretic separation has been obtained for products of 7 loci. The analysis of allele segregation of heterozygous trees confirms monogenic inheritance of the allele variants revealed.